2021
DOI: 10.1177/0300060520973137
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analyses of long noncoding RNAs and mRNAs in the progression of breast cancer

Abstract: Objective The objective was to explore the expression and potential functions of long noncoding RNA (lncRNA) and mRNAs in human breast cancer (BC). Methods Differentially expressed lncRNAs and mRNAs were identified and annotated in BC tissues by using the Agilent human lncRNA assay (Agilent Technologies, Santa Clara, CA, USA) and RNA sequencing. After identification of lncRNAs and mRNAs through quantitative reverse transcription polymerase chain reaction, we conducted a series of functional experiments to conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…We studied the changes in the immune genome profile in primary ESCA and uncovered its possible underlying molecular mechanisms. The KEEG analysis revealed that these IRGs were enriched in the cytokine-cytokine receptor interaction pathway, which reflects previous findings that these pathways play a crucial role in the proliferation, immune responses, and progression in several cancers (24)(25)(26). The dysregulation of cytokine interactions is also involved in the pathogenesis of ESCA (27).…”
Section: Discussionsupporting
confidence: 82%
“…We studied the changes in the immune genome profile in primary ESCA and uncovered its possible underlying molecular mechanisms. The KEEG analysis revealed that these IRGs were enriched in the cytokine-cytokine receptor interaction pathway, which reflects previous findings that these pathways play a crucial role in the proliferation, immune responses, and progression in several cancers (24)(25)(26). The dysregulation of cytokine interactions is also involved in the pathogenesis of ESCA (27).…”
Section: Discussionsupporting
confidence: 82%
“…Their dysregulation and abnormal expression patterns are associated with various cancer types, including TNBC [ 20 , 21 ]. The lncRNA, SNHG14, induces BC resistance to trastuzumab through H3K27 acetylation-mediated regulation of PABPC1 expression, lncRNA GHSROS significantly promotes growth and migration of BC, and lncRNA NONHSAT101069 regulates Twist1 by targeting the microRNA, miR-129-5p, to induce epirubicin resistance and promote BC cell migration and invasion [ 22 ]. In addition, a novel lncRNA named RP11-22N19.2 was highly overexpressed in TNBC compared with non-TNBC tissues, which predicted poor prognosis for overall survival and recurrence-free survival in TNBC [ 23 ].…”
Section: Introductionmentioning
confidence: 99%